PSII-6 Lysine-induced stimulation of proliferation, differentiation and migration in swine satellite cells is mediated by the mTORC1 and FAK pathways. (7th December 2018) - Jin, C; Gao, C; Zhang, Z; Yan, H; Wang, X
Abstract: In pig industry, Lysine (Lys) as the first limiting amino acid has been thought to promote muscle fiber hypertrophy by increasing protein synthesis. However, the functions of Lys seem far more complex than that. Seriously, in spite of satellite cells (SCs) take great role in muscle growth, the communication between Lys and SCs still unclear. The objective of this study was to investigate whether Lys could work as a signal regulatory factor to guide the proliferation, differentiation and migration of SCs through mammalian target of rapamycin complex 1 (mTORC1) and focal adhesion kinase (FAK) pathways. In current work, an undersupply of Lys reduced cell proliferation and increased apoptosis of SCs (P < 0.05). Additionally, phosphorylation of mTOR, ribosomal protein S6 kinase 1 and eukaryotic translation initiation factor 4E-binding protein 1 were significantly decreased (P < 0.05). Interestingly, we found cell proliferation was rescued after Lys added to sufficiency for 48 h (P>0.05) with reactivated mTORC1 pathway (P < 0.05). Moreover, cell fusion index showed the differentiation ability was weakened by Lys insufficiency (P < 0.05), proteins of mTORC1 pathway and myogenic factor family were significantly decreased (P < 0.05) by Lys deficiency after SCs differentiated for 48 h (P < 0.05). The differentiation ability was rescued after Lys re-supplementation for another 48 h (P>0.05). Cell wound healing and transwell assays indicated a significantly inhibition of migration ability by Lys deficiency (P < 0.05). Furthermore, phosphorylation of FAK, paxillin, protein kinase B and integrin β3 were significantly suppressed (P < 0.05). Cell migration was rescued after Lys added to sufficiency for 6 h (P>0.05) and proteins of FAK pathway was reactivated (P < 0.05) compared with the Lys deficiency group. In conclusion, these findings showed that Lys-dependent SCs proliferation, migration and differentiation are mediated by the mTORC1 and FAK signaling pathways, indicating Lys promotes muscle growth by activating SCs functions, not only a molecule block for protein synthesis.